2015
DOI: 10.1073/pnas.1501548112
|View full text |Cite
|
Sign up to set email alerts
|

Spray-combustion synthesis: Efficient solution route to high-performance oxide transistors

Abstract: Metal-oxide (MO) semiconductors have emerged as enabling materials for next generation thin-film electronics owing to their high carrier mobilities, even in the amorphous state, large-area uniformity, low cost, and optical transparency, which are applicable to flat-panel displays, flexible circuitry, and photovoltaic cells. Impressive progress in solution-processed MO electronics has been achieved using methodologies such as sol gel, deep-UV irradiation, preformed nanostructures, and combustion synthesis. Neve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
187
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 181 publications
(196 citation statements)
references
References 55 publications
6
187
3
Order By: Relevance
“…[ 9c , 17 ] Note that the large leakage currents of the spincoated CS fi lms refl ect nanoscale pinholes/porosity reasonably caused by gas evolution during combustion. [ 7 ] Furthermore, the present SCS fi lms exhibit far higher breakdown fi elds (Figure 1 c) than spin-coated CS fi lms and spin-coated, bar-coated, or spray-pyrolysis dielectric fi lms. [ 2d , 4a , 9c , 12 ] For example, the highest breakdown fi eld for the present SCS ZrO 2 fi lms (300 °C) reaches 9.5 MV cm −1 , 3-6× greater than that of spin-coated and spray-pyrolysis ZrO 2 fi lms processed at 450 °C.…”
Section: Wileyonlinelibrarycommentioning
confidence: 90%
See 3 more Smart Citations
“…[ 9c , 17 ] Note that the large leakage currents of the spincoated CS fi lms refl ect nanoscale pinholes/porosity reasonably caused by gas evolution during combustion. [ 7 ] Furthermore, the present SCS fi lms exhibit far higher breakdown fi elds (Figure 1 c) than spin-coated CS fi lms and spin-coated, bar-coated, or spray-pyrolysis dielectric fi lms. [ 2d , 4a , 9c , 12 ] For example, the highest breakdown fi eld for the present SCS ZrO 2 fi lms (300 °C) reaches 9.5 MV cm −1 , 3-6× greater than that of spin-coated and spray-pyrolysis ZrO 2 fi lms processed at 450 °C.…”
Section: Wileyonlinelibrarycommentioning
confidence: 90%
“…We and others have shown that well-patterned/defi ned gate/semiconductor layers yield greatly enhanced performance (turn-on characteristics, I on / I off ratios, better bias stress stability) than the crudely patterned/unpatterned TFTs based on the same materials stack. [ 7 ] Encouraged by the promising TFT performance using combined SCS-derived dielectric and semiconducting layers, conducting ZITO-coated AryLite substrates were next utilized to replace the rigid Si wafers, [ 20 ] and to realize fl exible IZO TFTs Figure S11 (Supporting Information), these devices with SCS-derived Al 2 O 3 or ZrO 2 dielectrics processed at 275 °C exhibit TFT characteristics with operating voltages below 3 V and an average mobilities of 3.9 ± 2.2 cm 2 V −1 s −1 and 6.2 ± 3.2 cm 2 V −1 s −1 for Al 2 O 3 /IZO and ZrO 2 /IZO devices, respectively. In addition, only slight decreases in mobilities for both devices were observed after bending for 10 cycles at radius of 15 mm.…”
Section: Wileyonlinelibrarycommentioning
confidence: 99%
See 2 more Smart Citations
“…
by X-ray refl ectivity has shown that spray-pyrolysis fi lms of materials such as indium-gallium-zinc oxide have signifi cantly lower porosity than spin-coated fi lms of a comparable thickness, [ 12 ] ultimately leading to improved mobility and bias-stress stability.Although spray pyrolysis offers the potential to deposit highquality TCOs at a low cost over large areas, it remains a blanket deposition technique that requires more expensive patterning techniques such as photolithography and etching for fabricating multilayer patterned structures such as thin-fi lm transistors. [ 13 ] These additional patterning steps limit throughput and contribute additional process complexity and cost.
…”
mentioning
confidence: 99%